Study of the Solar Collectors with Evacuated Tubes (International Journal of Innovative Research in Computer Science & Technology, 2021)
Solar thermal collector systems allow solar  energy to be used for cooling and heating. A heat transfer  fluid is utilized in these collectors to transmit collected  solar energy to applications that need it. Scientists have  proposed various collector designs and better collection  materials to enhance the solar collector's conversion  efficiency. The use of Nano fluids to study solar collectors  utilizing evacuated tubes is discussed in this article. The  researchers used a two-step method to prepare Nano fluids, which improved nano fluid stability. Swasco laboratories in  Mumbai provided the nanoparticles. Nanoparticles were  mixed in distilled water and well blended before being used  in the heat pipes. In this work, the Nano fluids were made  in two stages, which enhanced nano fluid stability. Before  being put in the heat tubing, the nanoparticle was well  mixed with distilled water. Most solar collectors may be  able to enhance their overall performance by using nano  fluids. However, unless a few issues about nano fluid  stability, overall performance, and hysteresis expectedness  are addressed, the full potential of Nano fluids in heat  transfer applications will not be realized.
Keywords: Collector; Heat; Nanoparticle; Water